Masseter muscle cysticercosis: a common disease with uncommon presentation - Chaurasia, Rameshwar Nath (BMJ Publishing Group, 2013)
Cysticercosis in humans is caused by Taenia solium larvae infestation. Oral cysticercosis is a rare condition and is challenging to diagnose. We present a case of masseter cysticercosis in a young woman who presented with painful recurrent cheek swelling. Diagnosis confirmed it after neuroimaging and histopathological examination of the excised lesion from masseter muscle.